Motor functional connectivity analysis of brain control network on high level athletes with fMRI research - Li, J.; Du, C.; Chen, M.; Li, K.; Xue, J.; Teng, C.; Hou, L. (Exercise Biochemistry Review, 2018)
Objective The nervous system is the control center that performs the function of the human body, including each nucleus of the cerebral cortex and basal ganglia, which can control the motion of the body through three pathways-direct pathway, indirect pathway and hyperdirect pathway. Long-term physical exercise can effectively improve the human respiratory and circulatory system function indicators and promote the development of nervous system.In order to discuss the mechanisms of the high level athletes' control of the brain function network and provide the experimental basis for the study of the motor control of the central nervous system, this research collects the activation images of the cortex and basal ganglia nuclei of the ordinary college students and the high level athletes and analyzes the function connection coefficient between the groups.